Delayed inflammation decrease is associated with mortality in Tocilizumab-treated critically ill SARS-CoV-2 patients: A retrospective matched-cohort analysis. Issue 1 (January 2022) - Urbina, Tomas; Lavillegrand, Jean-Rémi; Garnier, Marc; Mekinian, Arsene; Pacanowski, Jerome; Mario, Nathalie; Dumas, Guillaume; Hariri, Geoffroy; Pilon, Antoine; Darrivère, Lucie; Fartoukh, Muriel; Guidet, Bertrand; et al.
Little is known about the immuno-inflammatory response to Tocilizumab and its association with outcome in critically-ill SARS-CoV2 pneumonia. In this multicenter retrospective cohort of SARS-CoV-2 patients admitted to three intensive care units between March and April 2020, we matched on gender and SAPS II 21 Tocilizumab-treated patients to 42 non-treated patients. Need for mechanical ventilation was 76% versus 79%. IL-6, C-reactive protein, and fibrinogen had been collected within the first days of admission (T1), 3 d (T2) and 7 d (T3) later. Tocilizumab-treated patients had persistently higher IL-6 plasma levels and persistently lower C-Reactive protein and fibrinogen levels. Among Tocilizumab-treated patients, baseline levels of inflammatory biomarkers were not different according to outcome. Conversely, C-reactive protein and fibrinogen decrease was delayed in non-survivors. C-Reactive protein decreased at T1 in survivors (45 [30–98] vs 170 [69–204] mg/l, P  < 0.001) but only at T2 in non-survivors (37 [13–74] vs 277 [235–288], P  = 0.03). Fibrinogen decreased at T2 in survivors (4.11 [3.58–4.69] vs 614 [5.61–7.85] g/l, P  = 0.005) but not in non-survivors (4.79 [4.12–7.58] vs 7.24 [6.22–9.24] g/l, P  = 0.125). Tocilizumab treatment was thus associated with a persistent both increase in plasma IL-6, and decrease in C-reactive protein and fibrinogen. Among Tocilizumab-treated patients, the decrease in inflammatory biomarkers was delayed in non-survivors.